Preparation method of NiCo2O4-coated CeO2-ZrO2 / C supercapacitor electrode material

By doping CeO2-ZrO2/C in supercapacitor electrode material and generating caterpillar-like core-shell structure NiCo2O4@CeO2-ZrO2/C material, the problems of low conductivity and poor stability of existing NiCo2O4 materials are solved, and high Supercapacitor electrode material for specific capacity and cycle stability.

CN119400607APending Publication Date: 2025-02-07HUAINAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410789237.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-18
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing NiCo2O4 materials have problems such as low conductivity, low catalytic efficiency, poor stability in supercapacitors, and have harsh preparation process conditions and difficult operation.

Method used

The preparation method of NiCo2O4@CeO2-ZrO2/C supercapacitor electrode material is adopted. By doping NiCo2O4 with CeO2-ZrO2/C and annealing in air to form a caterpillar-like core-shell structure, the specific surface area and conductivity of the material are improved.

Benefits of technology

It significantly improves the conductivity and active sites of the electrode material, enhances the charge/electrolyte ion transfer rate, improves specific capacity and cycling stability, and solves the problems in material stability and preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400607A_ABST
    Figure CN119400607A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a NiCo2O4 (at) CeO2-ZrO2 / C supercapacitor electrode material, and belongs to the field of new energy material preparation, and the method comprises the steps: taking foamed nickel as a carrier, doping CeO2-ZrO2 / C in NiCo2O4 metal oxide, and then annealing a precursor doped with CeO2-ZrO2 / C in the air to generate a caterpillar-shaped core-shell structure NiCo2O4 (at) CeO2-ZrO2 / C. The NiCo2O4 (at) CeO2-ZrO2 / C supercapacitor electrode material has the advantages that the NiCo2O4 (at) CeO2-ZrO2 / C supercapacitor electrode material is prepared; the special structure provides an electron transmission channel, increases active sites and improves conductivity. The specific surface area of the electrode material is greatly increased, and the problem that the particle morphology is not easy to control in the prior art is solved. Compared with pure NiCo2O4, the electrocatalytic sites are increased, the activity is enhanced, and the electrode is high in activity and high in catalytic efficiency. The preparation method is simple, and compared with other methods, the preparation method has the advantages of simplicity in operation, environmental friendliness, low cost, high efficiency and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy material preparation, and more specifically, relates to a method for preparing a NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material. Background Art

[0002] Supercapacitors, which have the advantages of high power density, long life and low manufacturing cost, have faster charging and discharging speed and longer life than batteries, and have recently attracted people's attention and are generally considered to be one of the most promising energy storage systems. The growing demand for today's diverse energy storage applications has driven the development of high-power supercapacitors. Supercapacitors are ideal for applications that require high power density, such as portable electronic devices, fuel cell starting devices, space travel technology, hybrid vehicles, renewable energy systems and microelectronics. ] At the same time, the development of supercapacitor devices with huge area capacitance has also received strong attention recently to meet the needs of miniaturized consumer electronics, electric vehicles, and microelectronics-based energy systems. The improved energy density of supercapacitors is an important challenge, especially in applications that require large amounts of power and require sustained energy density. Hybrid supercapacitors have relatively high energy density, and metal oxides can be used as ideal materials for hybrid supercapacitors due to their special structural properties and electrochemical activity. At the same time, metal oxides can make up for the low capacity defects of carbon-based materials. Binary metal oxides such as NiCo2O4, MnCo2O4, CuCo2O4, and ZnCo2O4 are derived from alkaline Co3O4 spinel. Recent studies have shown that spinel-based binary metal oxides can provide excellent capacitance for supercapacitor materials. Among them, spinel NiCo2O4 is the most prominent, most notably affordable, environmentally friendly, low manufacturing cost, and low toxicity. Therefore, NiCo2O4 has received more attention in recent years and has become a more feasible and suitable alternative electrode component for high-performance supercapacitors. The NiCo2O4 phase can perfectly combine the oxides of Ni and Co to give full play to their synergistic effects. This will bring higher conductivity and ultra-high capacity than single oxides. However, there are still some challenges. NiCo2O4's relatively low conductivity and high brittleness limit the charge transfer rate, affecting the charge and discharge performance, and also limiting the rate performance and cycle stability of supercapacitors. In order to solve the above problems, the present invention provides the following technical solutions. Summary of the invention

[0003] The purpose of the present invention is to solve the shortcomings of NiCo2O4 material electrocatalysts prepared in the prior art, such as poor conductivity, low catalytic efficiency, poor stability, etc. when used in supercapacitors. At the same time, the preparation process also solves the shortcomings of the existing synthesis technology, such as harsh synthesis process conditions, poor operation, high energy consumption, etc.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing a NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material comprises the following steps:

[0006] S1, cutting, cleaning and drying the nickel foam to obtain a nickel foam matrix;

[0007] S2, weigh 3mmol Co(NO3)2·6H2O and Ni(NO3)2·6H2O and dissolve them in 20mL deionized water, then weigh 11mmol Co(NH2)2 and 5mmol NH4F and mix them to obtain a mixed solution A;

[0008] S3, the nickel foam matrix and the mixed solution A were placed in a 20 mL stainless steel reactor with a PTFE liner, placed in an oven for heat treatment, cooled to 20°C, taken out, washed and dried to obtain NiCo x O4 precursor;

[0009] S4. Place the precursor sample in a box furnace, set the annealing temperature to 350°C, keep warm for 2 hours, and the heating rate is 1°C·min -1 After cooling to room temperature, NiCo x O4 material;

[0010] S5, 0.02g CeO2-ZrO2 / C powder, 2mmol Co(NO3)2·6H2O, 1mmol Ni(NO3)2·6H2O and 20mL deionized water were mixed, and then 11mmol CO(NH2)2 and 5mmol NH4F were weighed and mixed to obtain a mixed solution B. After mixing, the NiCo obtained in step S4 was mixed. x The O4 material and mixed solution B were placed in a 20 mL stainless steel reactor with a PTFE liner, placed in an oven at 120°C for 12 h, cooled to 20°C, taken out, washed and dried;

[0011] S6. After heat treatment in a box furnace, cool to room temperature to obtain an electrode material.

[0012] Further, the preparation method of CeO2-ZrO2 / C powder is:

[0013] 2 mmol ZrCl4, CeCl3·7H2O and 2 mmol BDC were weighed and dissolved in 40 mL DMF to obtain a mixed solution. The mixed solution was vigorously stirred in a stirrer for 30 minutes, and 2 mL glacial acetic acid was added and stirred for 2 hours.

[0014] The reaction mixture was transferred into a 100 mL tellurium-lined stainless steel autoclave and kept at 120°C for 24 hours. After cooling to 25°C, the solid product was obtained by centrifugation, washed and dried, and the synthesized product was calcined in an Ar atmosphere to obtain CeO2-ZrO2 / C powder.

[0015] Furthermore, in step S2, the molar ratio of Co(NO3)2·6H2O to Ni(NO3)2·6H2O is 2:1, 1:1, 1:2 or 0:1.

[0016] Furthermore, in step S3, the heat treatment condition in the oven is 120° C. for 12 h;

[0017] Furthermore, in step S4, the annealing temperature in the box furnace is set to 350°C, the holding time is 2h, and the heating rate is 1°C·min -1 .

[0018] Furthermore, the molar ratio of ZrCl4 to CeCl3·7H2O is preferably 4:1, 3:2, 2:3, 1:4 or 0:1.

[0019] Furthermore, the muffle furnace programmed temperature method was used: heating at 800 °C for 2 h at a heating rate of 5 °C / min in an Ar atmosphere.

[0020] Furthermore, in step S6, the annealing temperature in the box furnace is set to 350°C, the holding time is 2h, and the heating rate is 1°C·min -1 .

[0021] The invention also discloses a NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material, which is prepared by the above-mentioned preparation method.

[0022] Beneficial effects of the present invention:

[0023] 1. A method for preparing a NiCo2O4@CeO2-ZrO2 / C high-performance supercapacitor electrode material of the present invention comprises doping NiCo2O4 metal oxide with CeO2-ZrO2 / C, and then annealing the CeO2-ZrO2 / C-doped precursor in air to generate a caterpillar-shaped core-shell structure NiCo2O4@CeO2-ZrO2 / C. This special structure provides an excellent electron transmission channel, greatly improves the specific surface area of ​​the electrode material, increases the active sites and conductivity of the material, and transfers charges / electrolyte ions faster, resulting in a higher specific capacity of the material. At the same time, it solves the problem of difficult control of particle morphology in the prior art. Compared with pure NiCo2O4, the electrocatalytic activity is further increased and the stability is enhanced, and it is an electrode with excellent electrochemical performance.

[0024] 2. The preparation method of the present invention adopts a simple hydrothermal method to prepare the precursor. Compared with other methods, it has the advantages of simple operation, environmental friendliness, low cost and high efficiency. The electrode efficiency and conductivity of the prepared electrode material are also significantly improved, thereby increasing the mass specific capacitance.

[0025] 3. The electrode material of the present invention has high electrocatalytic activity and cycle stability for redox reaction in alkaline medium, and the electrode material has high specific surface area and large cycle stability, which is crucial for realizing high-density electrochemical capacitor energy storage. The NiCo2O4@CeO2-ZrO2 / C composite material has a high specific surface area and large cycle stability at 1A·g -1 The scanning speed can provide 3332F·g -1 (1332.8C g -1 ) has a high specific capacitance at 10A·g -1 After 5000 cycles at a current density of 1.544 W, the specific capacitance retention rate of undoped NiCo2O4 was only 73.8%, and that of CeO2-ZrO2 / C was 56.6%. However, the specific capacitance retention rate of NiCo2O4@CeO2-ZrO2 / C reached 98%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The present invention will be further described below in conjunction with the accompanying drawings.

[0027] Figure 1 CV graphs of NiCo2O4@CeO2-ZrO2 / C, NiCo2O4 and CeO2-ZrO2 / C supercapacitors;

[0028] Figure 2 EIS curves of NiCo2O4@CeO2-ZrO2 / C, NiCo2O4 and CeO2-ZrO2 / C electrodes;

[0029] Figure 3Constant current charge and discharge curves of NiCo2O4@CeO2-ZrO2 / C, NiCo2O4 and CeO2-ZrO2 / C supercapacitors;

[0030] Figure 4 This is a graph showing the change in specific capacitance retention rate of NiCo2O4@CeO2-ZrO2 / C composite supercapacitor after 5000 constant current charge and discharge tests at 10A / g;

[0031] Figure 5 This is a curve diagram of the change in specific capacitance retention rate of the NiCo2O4@CeO2-ZrO2 / C composite supercapacitor after 5000 constant current charge and discharge tests at 10 A / g in this embodiment. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] A method for preparing a NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material comprises the following steps:

[0035] (1) First, the nickel foam is cut into nickel foam sheets of suitable size, cleaned, and dried for standby use;

[0036] (2) 3 mmol of Co(NO3)2·6H2O and Ni(NO3)2·6H2O were weighed and dissolved in 20 ml of deionized water, and then 11 mmol of Co(NH2)2 and 5 mmol of NH4F were weighed and mixed, and the mixed solution was magnetically stirred for 30 min to obtain a pink solution. The molar ratio of Co(NO3)2·6H2O to Ni(NO3)2·6H2O was 2:1, 1:1, 1:2 or 0:1, and in this embodiment, 1:1 was preferred;

[0037] (3) The pretreated nickel foam substrate and the mixed solution were placed in a 20 ml stainless steel reactor with a PTFE liner and placed in an oven at 120°C for 12 h. After cooling to 20°C, the sample was taken out and repeatedly rinsed with acetone and anhydrous ethanol, and finally dried in a vacuum oven at 60°C for 720 min to obtain NiCo x O4 precursor;

[0038] (4) taking out the nickel foam sheet with the pink precursor from the autoclave, washing it, and vacuum drying it;

[0039] (5) Place the prepared precursor sample in a box furnace, set the annealing temperature to 350°C, the holding time to 2 h, and the heating rate to 1°C min -1 After cooling to room temperature, the surface of the nickel foam sample was observed to change from pink to black, and NiCo x O4 material;

[0040] (6) Weigh 2 mmol ZrCl4 and CeCl3·7H2O and 2 mmol BDC and dissolve them in 40 ml DMF to obtain a mixed solution. The mixed solution is vigorously stirred in a stirrer for 30 minutes, and a modulator (2 ml glacial acetic acid) is added and stirred for 2 hours. The molar ratio of ZrCl4 to CeCl3·7H2O is 4:1, 3:2, 2:3, 1:4 or 0:1, and is preferably 3:2 in this embodiment;

[0041] (7) The reaction mixture was transferred to a 100 ml tellurium-lined stainless steel autoclave and kept at 120°C for 24 hours. After cooling to 25°C, the solid product was obtained by centrifugation. It was then washed three times with DMF and acetone respectively. The solid product was vacuum dried at 120°C for 12 hours. The synthesized product was heated at 800°C in an Ar atmosphere at a heating rate of 5°C / min for 2 hours. CeO2-ZrO2 / C with different ratios of cerium and zirconium were obtained;

[0042] (8) 0.02g CeO2-ZrO2 / C powder, 2mmol Co(NO3)2·6H2O, 1mmol Ni(NO3)2·6H2O and 20ml deionized water, then weigh 11mmol CO(NH2)2 and 5mmol NH4F, and mix them. Stir the mixed solution magnetically for 30min. Place the nickel foam and the mixed solution in a 20ml stainless steel reactor with PTFE lining, and place it in an oven at 120℃ for 12h. Cool to 20℃, take out the sample, rinse it repeatedly with acetone and anhydrous ethanol, and finally dry it in a vacuum oven at 60℃ for 720min.

[0043] (9) Next, place it in a box furnace and set the annealing temperature to 350°C, the holding time to 2 h, and the heating rate to 1°C min -1 After cooling to room temperature, a high-specific-surface-area caterpillar-shaped NiCo2O4@CeO2-ZrO2 / C high-performance supercapacitor electrode material can be obtained.

[0044] In this embodiment, NiO@C / Co3O4 / NF has high energy density and power density as well as long-term cycle stability. -1Can provide 1842.5F·g -1 The prepared supercapacitor (1×1cm) was charged for 30s and lit up for 5 minutes with 4 3W small bulbs in parallel; in addition, in order to test its long-term static stability, the supercapacitor device was placed for a few days and then subjected to CV test. The results showed that NiO@C / Co3O4 / NF / / AC (activated carbon electrode) could still retain 88% of its initial capacitance after one month.

[0045] Figure 1 is the SEM image of the NiCo2O4@CeO2-ZrO2 / C composite material in this embodiment;

[0046] Figure 2 CV graphs of NiCo2O4@CeO2-ZrO2 / C, NiCo2O4 and CeO2-ZrO2 / C supercapacitors in this embodiment;

[0047] Figure 3 EIS curves of NiCo2O4@CeO2-ZrO2 / C, NiCo2O4 and CeO2-ZrO2 / C electrodes in this implementation;

[0048] Figure 4 : The constant current charge and discharge curves of NiCo2O4@CeO2-ZrO2 / C, NiCo2O4 and CeO2-ZrO2 / C supercapacitors in this embodiment;

[0049] Figure 5 This is a curve diagram of the change in specific capacitance retention rate of the NiCo2O4@CeO2-ZrO2 / C composite supercapacitor after 5000 constant current charge and discharge tests at 10 A / g in this embodiment.

[0050] Example 2

[0051] (1) First, the nickel foam is cut into nickel foam sheets of suitable size, cleaned, and dried for standby use;

[0052] (2) Weigh 3 mmol Co(NO3)2·6H2O and Ni(NO3)2·6H2O and dissolve them in 20 mL of deionized water, then weigh 11 mmol Co(NH2)2 and 5 mmol NH4F and mix them. The mixed solution is magnetically stirred for 30 min to obtain a pink solution. The molar ratio of Co(NO3)2·6H2O to Ni(NO3)2·6H2O is 2:1.

[0053] (3) The pretreated nickel foam substrate and the mixed solution were placed in a 20 mL stainless steel reactor with a PTFE liner and placed in an oven at 120°C for 12 h. After cooling to 20°C, the sample was taken out and repeatedly rinsed with acetone and anhydrous ethanol, and finally dried in a vacuum oven at 60°C for 720 min to obtain NiCo x O4 precursor;

[0054] (4) taking out the nickel foam sheet with the pink precursor from the autoclave, washing it, and vacuum drying it;

[0055] (5) Place the prepared precursor sample in a box furnace, set the annealing temperature to 350°C, the holding time to 2 h, and the heating rate to 1°C min -1 After cooling to room temperature, the surface of the nickel foam sample was observed to change from pink to black, and NiCo x O4 material;

[0056] (6) Weigh 2 mmol ZrCl4 and CeCl3·7H2O and dissolve them together with 2 mmol BDC in 40 mL DMF to obtain a mixed solution. The mixed solution was vigorously stirred in a stirrer for 30 minutes, and a modulator (2 mL glacial acetic acid) was added and stirred for 2 hours. The molar ratio of ZrCl4 to CeCl3·7H2O was 3:2.

[0057] (7) The reaction mixture was transferred to a 100 mL tellurium-lined stainless steel autoclave and kept at 120°C for 24 hours. After cooling to 25°C, the solid product was obtained by centrifugation. It was then washed three times with DMF and acetone, respectively. The solid product was vacuum dried at 120°C for 12 hours. The synthesized product was heated at 800°C in an Ar atmosphere at a heating rate of 5°C / min for 2 hours. CeO2-ZrO2 / C with different ratios of cerium and zirconium was obtained;

[0058] (8) 0.02g CeO2-ZrO2 / C powder, 2mmol Co(NO3)2·6H2O, 1mmol Ni(NO3)2·6H2O and 20mL deionized water, then weigh 11mmol CO(NH2)2 and 5mmol NH4F and mix them, and stir the mixed solution magnetically for 30min. Place the nickel foam and the mixed solution in a 20mL stainless steel reactor with PTFE lining, and place it in an oven at 120℃ for 12h. Cool to 20℃, take out the sample, rinse it repeatedly with acetone and anhydrous ethanol, and finally dry it in a vacuum oven at 60℃ for 720min;

[0059] (9) Next, place it in a box furnace and set the annealing temperature to 350°C, the holding time to 2 h, and the heating rate to 1°C min -1After cooling to room temperature, a high-specific-surface-area caterpillar-shaped NiCo2O4@CeO2-ZrO2 / C high-performance supercapacitor electrode material can be obtained.

[0060] In this embodiment, NiO@C / Co3O4 / NF has high energy density and power density as well as long-term cycle stability. -1 Can provide 3332F·g -1 The prepared supercapacitor (1×1cm) was charged for 30s and 20 3W small bulbs in parallel were continuously lit for 6 minutes; in addition, in order to test its long-term static stability, the supercapacitor device was placed for a few days and then subjected to CV test. The results showed that NiO@C / Co3O4 / NF / / AC (activated carbon electrode) could still retain 92% of its initial capacitance after one month.

[0061] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material, characterized in that: The steps include: S1, cutting, cleaning and drying the nickel foam to obtain a nickel foam matrix; S2, weigh 3mmol Co(NO3)2·6H2O and Ni(NO3)2·6H2O and dissolve them in 20mL deionized water, then weigh 11mmol Co(NH2)2 and 5mmol NH4F and mix them to obtain a mixed solution A; S3, the nickel foam matrix and the mixed solution A were placed in a 20 mL stainless steel reactor with a PTFE liner, placed in an oven for heat treatment, cooled to 20°C, taken out, washed and dried to obtain NiCo x O4 precursor; S4. Place the precursor sample in a box furnace, set the annealing temperature to 350°C, keep warm for 2 hours, and the heating rate is 1°C·min -1 After cooling to room temperature, NiCo x O4 material; S5, 0.02g CeO2-ZrO2 / C powder, 2mmol Co(NO3)2·6H2O, 1mmol Ni(NO3)2·6H2O and 20mL deionized water were mixed, and then 11mmol CO(NH2)2 and 5mmol NH4F were weighed and mixed to obtain a mixed solution B. After mixing, the NiCo obtained in step S4 was mixed. x The O4 material and mixed solution B were placed in a 20 mL stainless steel reactor with a PTFE liner, placed in an oven at 120°C for 12 h, cooled to 20°C, taken out, washed and dried; S6. After heat treatment in a box furnace, cool to room temperature to obtain an electrode material.

2. The method for preparing a NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material according to claim 1, characterized in that: The preparation method of CeO2-ZrO2 / C powder is as follows: Weigh 2mmol ZrCl4, CeCl3·7H2O and 2mmol BDC and dissolve them in 40mL DMF to obtain a mixed solution. Stir the mixed solution vigorously in a stirrer for 30 minutes, add 2mL glacial acetic acid and continue stirring for 2h; The reaction mixture was transferred into a 100 mL tellurium-lined stainless steel autoclave and kept at 120°C for 24 hours. After cooling to 25°C, the solid product was obtained by centrifugation, washed and dried, and the synthesized product was calcined in an Ar atmosphere to obtain CeO2-ZrO2 / C powder.

3. The method for preparing a NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material according to claim 1, characterized in that: In step S2, the molar ratio of Co(NO3)2·6H2O to Ni(NO3)2·6H2O is 2:1, 1:1, 1:2 or 0:

1.

4. The method for preparing a NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material according to claim 1, characterized in that: The heat treatment condition in the oven in step S3 is 120° C. for 12 h.

5. The method for preparing a NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material according to claim 1, characterized in that: In step S4, the annealing temperature in the box furnace is set to 350°C, the holding time is 2h, and the heating rate is 1°C·min -1 .

6. The method for preparing a NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material according to claim 2, characterized in that: The molar ratio of ZrCl4 to CeCl3·7H2O is preferably 4:1, 3:2, 2:3, 1:4 or 0:

1.

7. The method for preparing a NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material according to claim 2, characterized in that: Muffle furnace programmed temperature method: heating at 800 °C for 2 h at a heating rate of 5 °C / min in an Ar atmosphere.

8. The method for preparing a NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material according to claim 1, characterized in that: In step S6, the annealing temperature in the box furnace is set to 350°C, the holding time is 2h, and the heating rate is 1°C·min -1 .

9. A NiCo2O4@CeO2-ZrO2 / C supercapacitor electrode material, characterized in that: Prepared according to any one of claims 1 to 8.